Epigenetic control of hypersensitivity in chronic inflammatory pain by the de novo DNA methyltransferase Dnmt3a2 - Oliveira, Ana; Litke, Christian; Paldy, Eszter; Kuner, Rohini; Bading, Hilmar; Mauceri, Daniela (Molecular pain, 2019)
Chronic pain is a pathological manifestation of neuronal plasticity supported by altered gene transcription in spinal cord neurons that results in long-lasting hypersensitivity. Recently, the concept that epigenetic regulators might be important in pathological pain has emerged, but a clear understanding of the molecular players involved in the process is still lacking. In this study, we linked Dnmt3a2, a synaptic activity-regulated de novo DNA methyltransferase, to chronic inflammatory pain. We observed that Dnmt3a2 levels are increased in the spinal cord of adult mice following plantar injection of Complete Freund’s Adjuvant, an in vivo model of chronic inflammatory pain. In vivo knockdown of Dnmt3a2 expression in dorsal horn neurons blunted the induction of genes triggered by Complete Freund’s Adjuvant injection. Among the genes whose transcription was found to be influenced by Dnmt3a2 expression in the spinal cord is Ptgs2, encoding for Cox-2, a prime mediator of pain processing. Lowering the levels of Dnmt3a2 prevented the establishment of long-lasting inflammatory hypersensitivity. These results identify Dnmt3a2 as an important epigenetic regulator needed for the establishment of central sensitization. Targeting expression or function of Dnmt3a2 may be suitable for the treatment of chronic pain.